Proposed Amendment of the Articles of Agreement Regarding Basic Votes : Preliminary Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Paragraph 4 of the Board of Governors Resolution on Quota and Voice Reform in the International Monetary Fund, which was adopted effective September 18, 2006 (Resolution 61-5), addresses issues relating to the reform of basic votes in the Fund. Specifically, it provides as follows: 'As an integral part of the reform program, and together with its recommendations for increases in quotas under paragraph 3, the Executive Board is requested to propose to the Board of Governors an amendment of the Fund's Articles of Agreement that would: (a) provide for at least a doubling of the 'basic' votes that each member possesses pursuant to Article XII, Section 5(a) of the Fund's Articles of Agreement, and thereby at a minimum protect the existing voting share of low income countries as a group and (b) ensure that the ratio of the sum of the 'basic' votes of all members to the sum of members' total voting power remains constant following the increase under (a) above in the event of any subsequent changes in the total voting power of members. The Executive Board is requested to put forward a specific proposal by the Annual Meetings in 2007, and no later than the Annual Meetings in 2008.' This paper is intended as a first step in facilitating the Executive Board's response to the above request of the Board of Governors. Specifically, it discusses the design of an amendment of the Articles that would ensure that the ratio of the sum of the basic votes of all members to the sum of members' total voting power remains constant, as called for in paragraph 4(b) of Resolution 61-5, and identifies implications of such an amendment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Amendment; Basic Vote; PP; Vote Adjustment; Vote